SUPPORTED BUILD OPERATE TRANSFER EFFECTIVENESS ANALYSIS TO IMPROVE FINANCIAL FEASIBILITY OF TOLL ROADS IN INDONESIA - Tamin, Rizal Z.; Mahani, Iris; Marzuki, Puti F. (Jurnal HPJI, 2017)
Abstract This paper is aimed to analyze Supported Build Operate Transfer as an alternative toll road development financing scheme in the Public Private Partnership framework. Support alternatives analyzed include construction grant, operation grant, tax holiday, and soft loan. The adopted approach consists of classifying groups of non-financially feasible toll roads based on the main causes, analyzing effective support alternative for each group, and performing sensitivity analysis to measure the relationship between the condition of financial infeasibility and the extent of the needed support. Analysis results show that the most effective support is construction grant (investment cost) and operation grant (revenue improvement) while supports in form of tax reduction or decrease of discount rate are very marginal. The analysis also indicate that Supported Build Operate Transfer is effective to be granted to toll roads that need relatively high investment cost but have low revenue. Meanwhile, for toll roads that need high investment cost and have high revenue, it is not suggested to apply Supported Build Operate Transfer. For toll roads with low investment cost and low revenue, the government has to get involved by applying Availability Based Payment scheme as in this case, besides support at initial phase, support during operation phase would also be needed. Keywords: toll road, Public Private Partnership, Supported Build Operate Transfer, Availability Based Payment  Abstrak Makalah ini bertujuan untuk menganalisis Supported Build Operate Transfer sebagai alternatif skema pembiayaan pembangunan jalan tol dalam kerangka Kerjasama Pemerintah dan Badan Usaha. Dukungan alternatif yang dianalisis meliputi hibah konstruksi, hibah operasi, tax holiday, dan soft loan. Pendekatan yang diadopsi terdiri atas penggolongan kelompok jalan tol yang tidak layak secara finansial berdasarkan penyebab utamanya, menganalisis alternatif dukungan yang efektif untuk masing-masing kelompok, dan melakukan analisis sensitivitas untuk mengukur hubungan antara kondisi ketidakseimbangan keuangan dan tingkat dukungan yang dibutuhkan. Hasil analisis menunjukkan bahwa dukungan yang paling efektif adalah hibah konstruksi (investment cost) dan hibah operasi (revenue improvement) sementara dukungan dalam bentuk pengurangan pajak atau penurunan tingkat diskonto sangat marjinal. Analisis juga menunjukkan bahwa Supported Build Operate Transfer efektif untuk diberikan pada jalan tol yang membutuhkan biaya investasi yang relatif tinggi namun memiliki pendapatan rendah. Sedangkan untuk jalan tol yang mem-butuhkan biaya investasi tinggi dan memiliki pendapatan tinggi, tidak disarankan untuk menerapkan Supported Build Operate Transfer. Untuk jalan tol dengan biaya investasi rendah dan pendapatan rendah, pemerintah harus terlibat dengan menerapkan skema Available Based Payment, seperti pada kasus ini, selain dukungan pada tahap awal, dukungan selama tahap operasi juga akan dibutuhkan. Kata-kata kunci: jalan tol, Kerjasama Pemerintah dan Badan Usaha, Supported Build Operate Transfer, Availability Based Payment